Expression of Serpin Peptidase Inhibitor B2 (SERPINB2) is regulated by Aryl hydrocarbon receptor (AhR). (25th August 2019) - Brauze, Damian; Kiwerska, Katarzyna; Bednarek, Kinga; Grenman, Reidar; Janiszewska, Joanna; Giefing, Maciej; Jarmuz-Szymczak, Malgorzata
Abstract: Aryl hydrocarbon receptor (AhR) is a highly conserved ligand-activated transcription factor with high affinity to aromatic planar compounds, such as β-naphthoflavone (BNF), benzo[a]pyrene (BaP) or dioxin (TCDD). After binding the ligand, AhR triggers induction of the expression of phase I and phase II drug-metabolizing genes, together with numerous other genes that are not directly involved in the metabolism of xenobiotics. Several studies have shown that AhR plays a role in tumor initiation, promotion and progression, but the molecular mechanisms involved in these processes are not fully understood. A previous study from our laboratory indicated that the SERPINB2 gene is presumably regulated by AhR. To prove that such induction is really AhR-dependent, in the present study we knocked down the expression of AhR by stable transfection of a laryngeal squamous cell carcinoma cell line (UT-SCC-34) with shRNA, resulting in 92% reduction of BNF-induced expression of SERPINB2 . However, in silico analysis did not reveal AhR-dependent responsive elements in the promoter of the SERPINB2 gene. Therefore, to address this problem, we have used cycloheximide, an inhibitor of translation, and our results clearly indicate that an additional, newly synthesized protein is involved in AhR-dependent induction of SERPINB2 expression by BNF. So, to exclude that AhR binds to the putative xenobiotic-responsive elements (XREs) localized upstream of the SERPINB2 gene, we performed chromatin immunoprecipitation assays. As expected, we found no direct binding of AhR to its responsive elements in the vicinity of the SERPINB2 gene, further demonstrating the indirect SERPINB2 induction by AhR. However, the further analysis demonstrated that the expression of the enhancer RNA encoded by the region of DNA 20 kbp upstream from the SERPINB2 gene was AhR-dependent. Although AhR-mediated SERPINB2 induction clearly requires the synthesis of an additional protein, the kinetics of SERPINB2 induction is as fast as the kinetics of CYP1A1 and CYP1B1 induction (both genes directly regulated by AhR). Therefore, given previous studies regarding the induction of SERPINB2 expression by bacterial lipopolysaccharides (LPS), we think that, similarly, the interaction with pause-release proteins may be responsible for AhR-dependent regulation of SERPINB2 expression. Highlights: Expression of the SERPINB2 is inducible by Ah receptor ligands. Knockdown of AhR by RNA interference reduce the induction of SERPINB2 expression. Newly synthesized protein is involved in the induction (CHX experiments). Direct AhR binding to the sequences preceded SERPINB2 gene was not necessary for the induction (CHIP). We have reported AhR-dependent induction of enhancer RNA localized 18K prior SERPINB2 transcription start site.